Ritual, teatro y performance en un culto al niño dios y al diablo. Las pastorelas de la región purépecha, Michoacán (México) - Elizabeth Araiza (Journal de la Société des Américanistes)
The Christmas pageant (pastorela) is, in principle, a living and dialogical representation that evokes the birth of Jesus, the zeal of the shepherds to celebrate that event, and the attempts by the Devil to impede them. In the P’urhépecha region we attended an event that interweaves various modalities of acting, each one of which brings to life distinct sensorial universes and multiple referents. When staged in urban contexts these events have been seen as a theatrical genre, but when performed in rural and indigenous areas they are considered a mode of ritual. Describing a specific case and putting various pastorelas staged by P’urhépechas into comparative perspective allows us to demonstrate that this event combines theater and ritual without one superimposing itself on the other or preceding it in an evolutionary sense (as in « from ritual to theater »). The point is to contribute to a discussion of the difficulties entailed in the definitions of the modalities of acting – ritual, theater, games, performance, etc. – both individually and as a whole.